Pengaruh Kompetensi Pedagodik Guru Pendidikan Agama Kristen Terhadap Disiplin Belajar Siswa Kelas X SMA Negeri 1 Tanjung Pura Kabupaten Langkat Tahun Pembelajaran 2023/2024 - Jonatan Fernando Siahaan; Malani Simanungkalit; Tiurma Berasa; Lustani Samosir; Risden Anakampun (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the influence of PAK teachers' pedagogical competence on the learning discipline of class "Senior High School 1 Tanjung Pura, Academic Year 2023/2024." The research method is quantitative descriptive inferential. The population is all class Random sampling (random sampling) was 30% of the total population, namely 35 people. The research instrument is a closed questionnaire. From the results of data analysis, it was obtained: a) The value rcount=0.579>rtabel=0.334 and tcount=4.079>ttable=2.042 shows that there is a positive and significant relationship between the pedagogical competence of PAK teachers and the learning discipline of class X students at SMA Negeri 1 Tanjung Pura for the 2023 Academic Year /2024. b) Regression equation. c) From the determination test it is known that the magnitude of the effect is 33.52%. d) Hypothesis testing obtained Fcount=16.49>Ftable=3.32 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the pedagogical competence of PAK teachers on the learning discipline of class X students at SMA Negeri 1 Tanjung Pura for the 2023/2024 academic year.